Thermal injuries from exploding electronic cigarettes. Issue 5 (August 2018) - Hickey, Sean; Goverman, Jeremy; Friedstat, Jonathan; Sheridan, Robert; Schulz, John
Highlights: Electronic cigarettes (ECs) are a new public health danger. The majority of EC burns occur in males that carry the devices in their pants pocket. EC explosions cause small TBSA burns that are deep 2nd and 3rd degree wounds. Abstract: Introduction: There are an estimated 2.75 million electronic cigarette (EC) users in the United States. ECs have become the most commonly used nicotine-containing product in young adults ages 18–24 years. Thermal, blast, and missile injuries from EC explosions has grown rapidly in recent years. Burn surgeons must remain up to date regarding management and treatment of burn injuries related to EC device ignition. Methods: An IRB approved retrospective review of all patients admitted to the Massachusetts General Hospital Burn Center from January 2015 to April 2017 was performed. Fourteen patients with injuries associated with EC use were identified. Patient demographics, injury location, size and degree of burn, treatments required, length of stay (LOS), time to 95% closure, associated complications and injuries, and the circumstances that led to the injury were identified. Results: The mean age was 28.6 ± 8.6 years with a range of 19–50 years (n = 14). EC burns occurred in males 93% (13/14) of the time. The majority of EC explosions caused 2nd and 3rd degree burns (57%) within the same wound bed, followed by deep 2nd degree (29%), and superficial 2nd degree (14%). The average TBSA from EC burns was 4.7 ± 2.4% with a range of 1–10%. The most common location of the device or battery at the time of the injury was a pant pocket 86% (12/14), followed by 7% hand (1/14) and 7% purse (1/14). Isolated lower extremity burns occurred in 43% (6/14) of patients, while lower extremity and hand burns occurred in 21% (3/14) of patients. Nine of 14 patients required an operating room encounter under general anesthesia. Eight of 14 patients required skin grafting for definitive wound closure. The mean hospital length of stay was 6.6 ± 4.7 days with a range of 0–15 days. Time to 95% wound closure was 18.4 ± 10.8 with a range of 8–40 days. Conclusion: Thermal and blast injuries associated with EC device failure tend to cause small TBSA burns that are deep 2nd and 3rd degree wounds. The most common location for EC device storage among males was the front pants pocket. EC device users should be made aware of the dangers associated with EC use and advised to carry EC devices away from their body in dedicated carrying cases without loose metallic items.